2002
DOI: 10.1182/blood.v99.4.1136
|View full text |Cite
|
Sign up to set email alerts
|

Germinal center phenotype and bcl-2 expression combined with the International Prognostic Index improves patient risk stratification in diffuse large B-cell lymphoma

Abstract: The International Prognostic Index (IPI) identifies poor-and good-risk patients with diffuse large B cell lymphoma (DLBCL); however, the majority of patients have an intermediate IPI, with an uncertain prognosis. To determine whether cellular factors can be combined with the IPI to more accurately predict outcome, we have analyzed 177 presentation nodal DLBCLs for the expression of bcl-2 and a germinal center (GC) phenotype (defined by expression of bcl-6 and CD10). P53 gene band shifts were detected using sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
213
4
5

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(244 citation statements)
references
References 58 publications
22
213
4
5
Order By: Relevance
“…Finally, we observed 14% of CD10 positivity suggesting a large amount of PBL of nongerminal center B-cell lymphoma (non-GCB), as shown by Yoshida et al who observed 15/ 15 non-GCB PBL [23]. Our results are therefore concordant with those that have been previously reported in PBL, as in DLBCLs [28,31,32,34,35,37] (Table III).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, we observed 14% of CD10 positivity suggesting a large amount of PBL of nongerminal center B-cell lymphoma (non-GCB), as shown by Yoshida et al who observed 15/ 15 non-GCB PBL [23]. Our results are therefore concordant with those that have been previously reported in PBL, as in DLBCLs [28,31,32,34,35,37] (Table III).…”
Section: Discussionsupporting
confidence: 92%
“…We found 71% of Bcl-2-positive tumor samples when more than 30% of the tumor cells were positive. This result was concordant with the 10/15 Bcl-2-positive PBL reported by Yoshiba et al [23] and the proportion of Bcl-2-positive DLBCLs reported in the literature [25][26][27][28][29][30][31][32][33][34][35][36]. Finally, we observed 14% of CD10 positivity suggesting a large amount of PBL of nongerminal center B-cell lymphoma (non-GCB), as shown by Yoshida et al who observed 15/ 15 non-GCB PBL [23].…”
Section: Discussionsupporting
confidence: 91%
“…Multiple studies have looked at the expression of bcl-2 using immunostains and most have found no difference in overall survival. 16,23,[27][28][29][30][31][32][33][34][35] However, some studies have found that bcl-2 expression is associated with a significantly worse overall survival, 3,[36][37][38][39][40][41][42] or event-free survival. [29][30][31]36,37 The discrepancies related to bcl-2 expression and prognosis may be related to the underlying subgroups of DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous promising cellular targets and assays have been identified, such as p53 [9,20], p16 INK4A [21], bcl-2 [22,23], bcl-6 [23,24], and gene expression profiling [25,26], none of these have gained the level of acceptance required to be routinely used for risk stratification in trials and other clinical settings. Until such biology-based markers have been validated and standardized, clinical factors will continue to be the foundation of prognosis assessment in DLBCL.…”
Section: Discussionmentioning
confidence: 99%